Effect of Current Ratio and Debt to Asset Ratio Against Return on Assets (Empirical Study on Pharmaceutical Sector Companies Listed on the Indonesia Stock Exchange (BEI) 2016 – 2020 Period) - Dijan Mardiati; Selvi Putri Permatasari (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of Current Ratio (CR) and Debt to Asset Ratio (DAR) on Return On Assets (ROA). The type of research used in this research is descriptive research that uses a quantitative approach. The type of data used in this research is secondary data. The data source used in this study is the financial statements of pharmaceutical sector companies listed on the Indonesia Stock Exchange for the 2016 – 2020 period . The sampling technique in this study used purposive sampling and obtained a research sample of 4 companies with a total of 20 research sample data. The analysis technique used descriptive statistical analysis, Chow test, Hausman test, then classic assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Then test multiple linear regression analysis, then test the hypothesis by using the t test, F test, and the coefficient of determination. Data analysis using software Eviews version 12. The results of this study indicate that the Current Ratio (CR) has a negative and significant effect on Return On Assets (ROA) based on the results of tcount 4.173648 > ttable 2.10982, with a significance value of 0.0009 less than 0.05. While the Debt to Asset Ratio (DAR) has no effect on Return On Assets (ROA) based on the results of the tcount 2.089533 < ttable 2.10982, with a significance value of t of 0.0554 which is greater than 0.05. Simultaneously Fcount 49.81422 > Ftable 3.59, with a probability significance value of 0.0008 less than 0.05, then the Current Ratio (CR), Debt to Asset Ratio (DAR) together have a significant effect on Return On Assets (ROA).